The Role of Human Resource Management in Employee Well-Being and Mental Health: A Systematic Literature Review - Mahdia, Asrini (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research is a systematic literature review on the role of Human Resource Management (HRM) in employee well-being and mental health. This literature review aims to identify HRM practices that influence employee well-being and mental health, as well as to evaluate their impact on organizational performance. The results of the literature review show that HRM practices such as working time flexibility, support from superiors and colleagues, career development opportunities, organizational justice and compensation policies, a healthy and safe work environment, recognition of achievements, participation and decision making opportunities play an important role in improving employee well-being and mental health. The implications of these findings support the need for organizations to prioritize the implementation of HRM practices oriented towards employee well-being as a strategy to improve overall organizational performance.